Successful lung transplantation from a donor with lung and ovarian masses. Issue 11 (5th November 2019) - Asif, Abuzar A; Narula, Tathagat; Erasmus, David B; Alvarez, Francisco; Nichols, Todd; Jacob, Samuel; Pham, Si M; Cortese, Cherise; Makey, Ian A
Abstract: Declining a donor when there is a reasonable possibility that the abnormality on chest imaging could be benign carries the risk of losing out on potentially usable lungs in an already parched landscape of donor organ availability. Cautiously aggressive attitudes to acceptance of borderline donors can help bridge the significant discrepancy that exists between the demand and availability of donor organs. Herein, we present a case highlighting successful bilateral lung transplantation from a relatively imperfect donor.